Evaluation of channel-like porous-structured titanium in mechanical properties and osseointegration. (1st May 2020) - Wang, Dong; He, Guo; Tian, Ye; Ren, Ning; Ni, Jiahua; Liu, Wei; Zhang, Xianlong
Abstract: The porous titanium with a channel-like pore structure fabricated by infiltration casting followed by selectively dissolving the precursor woven three dimensional (3D) structure technique was comprehensively investigated by means of mechanical tests, in vitro and in vivo evaluation. Such porous structure exhibited superiority in compressive, tensile strength and osseointegration. At 40% porosity, the average compressive and tensile strength reached about 145 MPa and 85 MPa, which was superior to that of other porous titanium, e.g., Selective Laser Melting or powder sintered ones, and was comparable to that of the human cortical bone. Without any bioactive surface treatment, this porous titanium exhibited good cell adhesion, rapid cell proliferation and excellent osseointegration. Based on the study, the 0.4 mm pore size resulted in the most rapid cell proliferation and the maximal BV/TV ratio and trabecular bone number of the new bone that ingrew into the porous titanium. To balance the excellent osseointegration and adequate mechanical properties, the optimal structural parameters were 0.4 mm pore size with 40% porosity. This porous titanium is very promising for orthopedic applications where compressive and tensile load-bearing is extremely important.